2008
DOI: 10.4049/jimmunol.180.1.655
|View full text |Cite
|
Sign up to set email alerts
|

IL-17RA and IL-17RC Receptors Are Essential for IL-17A-Induced ELR+ CXC Chemokine Expression in Synoviocytes and Are Overexpressed in Rheumatoid Blood

Abstract: IL-17A is a cytokine secreted by the newly described Th17 cells implicated in rheumatoid arthritis (RA). Less is known about its receptors in synoviocytes. IL-17RA and IL-17RC were found to be overexpressed in RA peripheral whole blood and their expression was detected locally in RA synovium. In vitro, IL-17A synergized with TNF-α to induce IL-6, IL-8, CCL-20, and matrix metalloproteinase-3. Using microarrays, a specific up-regulation of Glu-Leu-Arg+ CXC chemokines was observed in IL-17A-treated synoviocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 48 publications
11
98
1
2
Order By: Relevance
“…MIP-2 is a mouse homolog of human IL-8 (CXCL8), and CXCL8 expression was shown to be elevated and correlated with IL-17A levels and neutrophil counts in the sputum of asthmatic patients (21), indicating the involvement of CXC chemokines in the pathogenesis of neutrophilic airway inflammation in asthma. Previous studies suggested that IL-17 induces CXCL8 secretion from synoviocytes (26), as well as enhances IL-1b-induced CXC8 secretion in lung microvascular endothelial cells (27). Therefore, the upregulation of CXC chemokines in RORgt-tg mice may occur in a Th17 cell-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…MIP-2 is a mouse homolog of human IL-8 (CXCL8), and CXCL8 expression was shown to be elevated and correlated with IL-17A levels and neutrophil counts in the sputum of asthmatic patients (21), indicating the involvement of CXC chemokines in the pathogenesis of neutrophilic airway inflammation in asthma. Previous studies suggested that IL-17 induces CXCL8 secretion from synoviocytes (26), as well as enhances IL-1b-induced CXC8 secretion in lung microvascular endothelial cells (27). Therefore, the upregulation of CXC chemokines in RORgt-tg mice may occur in a Th17 cell-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in human synoviocytes, both IL-17RA and IL-17RC are required for IL-17A-induced chemokine expression (55). The necessity of IL-17RC for the functions of IL-17A and IL-17F is still under debate because of two observations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cells with high IL-17RC expression could be highly responsive to IL-17F, whereas those with low IL-17RC expression and high IL-17RA expression might respond better to IL-17A (5). In contrast, a number of studies have suggested that binding to the IL-17RC receptor might not be essential for the activity of IL-17A and IL-17F (11,31,35). Indeed, we found that secreted G-CSF protein was not detected following IL-17F stimulation of HRPTEC culture that significantly expressed IL-17RC on the cell surface, whereas significant G-CSF production was detected in IL-17F-stimulated primary human cortical epithelial cells that do not express IL-17RC.…”
Section: F247 Regulation Of G-csf By Il-17a In Renal Epithelial Cellsmentioning
confidence: 99%